2021
DOI: 10.1371/journal.pone.0253473
|View full text |Cite
|
Sign up to set email alerts
|

Children’s psychological well-being and problem behavior during the COVID-19 pandemic: An online study during the lockdown period in Germany

Abstract: As COVID-19 dramatically changes human social life, restrictive lockdown periods to slow the spread of the virus have been suggested to particularly affect the psychological well-being of children and their families. To capture lockdown-related effects on a large scale, the present study used an online questionnaire completed by parents of 3-10-year-olds during the most restrictive lockdown period in Germany thus far (N = 2,672). Parents reported their stress level, their child’s well-being, and their child’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 56 publications
5
72
2
1
Order By: Relevance
“…Although expected and in contrast to previous results, 2,12,17,18 the adverse consequences found do not largely differ according to socioeconomic status (SES): educational attainment of the mother was (only) signi cantly associated with emotional and behavioral di culties in boys (data not shown). A previous nationwide study from Germany revealed that children from families with low SES, limited living space, or migration background have been more affected by the pandemic.…”
Section: Discussioncontrasting
confidence: 88%
“…Although expected and in contrast to previous results, 2,12,17,18 the adverse consequences found do not largely differ according to socioeconomic status (SES): educational attainment of the mother was (only) signi cantly associated with emotional and behavioral di culties in boys (data not shown). A previous nationwide study from Germany revealed that children from families with low SES, limited living space, or migration background have been more affected by the pandemic.…”
Section: Discussioncontrasting
confidence: 88%
“…Families were affected by the COVID-19 pandemic and the associated lockdown measures on several levels: they had to reorganize many aspects of everyday life, e.g., compensating restricted childcare, which had an impact on working conditions. Children themselves were confronted with the interruption of their familiar, daily routines and their social life [ 1 ], resulting in decreased health-related quality of life and more mental health problems [ 2 , 3 , 4 ]. Established support services for families were restricted, making access and utilization more difficult [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parenting models (approaches, methods, strategies) for children greatly affect the cognitive, mental, and social development of children. Research conducted by Christner, et al [16] revealed that many children experience stress when they study at home, not only because they cannot meet and play with their friends at school, but also because parents have not found the best way to guide them to learn. Therefore, democratic parenting can certainly reduce the level of stress experienced by children at home.…”
Section: Literature Review Parenting Patterns and Children's Learning Activities During The Pandemicmentioning
confidence: 99%